Pemanfaatan Biji Keriput Kacang Tanah sebagai Benih - Agustina Asri Rahmianna; Joko Purnomo; Didik Harnowo (Iptek Tanaman Pangan, 2015)
State Law No. 12/92 on agricultural systems for food crops stated that good quality seeds is seeds of correct and pure variety with high genetic, physiological and physical qualities, and in accordance with the quality standard of its class. The demand for groundnut seeds were almost entirely fulfilled by informal seed supply, which may come from a traditional system (farmers use their own seeds), buying from agricultural shops that process their own harvested pods into seeds, or buying from informal seed growers. Whilst the certified seeds produced by official seed growers is very limited in amount and supplys only a small portion of the total national seed demand. Under such condition, selection for seed quality is mainly based on the physical seed condition, such as seed size, brightness of seed coat color, and maturity of seeds. In other words, farmers prefer to select sound mature kernels and reject the shriveled kernels. Research results, however, indicated that plants generated from shriveled kernels were not significantly different to those generated from pithy kernels in term of growth and pod yield. Given the high cost and limited stocks of seed during the high planting season, it is advisable seed sorting process is not too tight and the use of wrinkled seeds for planting is prioritized. When there are overstock seeds, it is suggested to keep the sound or pithy seeds or to consume these seeds for food safety issue. This is because research results showed that shriveled seeds are more susceptible to Aspergillus flavus infection and aflatoxin contamination than the pithy seeds.